Field experiment of polyculture technology of tiger shrimp (P. monodon Farb.) Milkfish (Chanos chanos Forskal), and Seaweed (Gracilaria verrucosa) in Brackhiswater water pond of Borimasunggu village, Maros regency - Markus Mangampa; Burhanuddin Burhanuddin (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2014)
Polyculture technology is the culture of various species of fish which has similar trophic level, where the organisms are perform biological and chemical processes in synergy with several advantages in the ecosystem. Field experiment was done in the brackhiswater ponds Borimasunggu vilage Maros regency, South Sulawesi, using 3 ponds of 1.0 ha pond-1. The research was aimed to apply the polyculture technology of tiger shrimp, fish and seaweed. Tiger shrimp yuvenile and milkfish yuvenile with the average weight of 0.056 ± 0.006 g and 75 ± 2.1 g. the seaweed is Gracillaria verrucosa. Stocking of seaweed performed 30 days earlier than tiger shrimp yuvenile and fish. Stocking density each pond are 1,500 kg sea weed + 30,000 tiger shrimps + 1,500 yuvenile of milk fish (A) and 1,500 kg sea weed+ 30,000 kg of tiger shrimps yuvenile (B); and (C) = 1,500 milkfish + 1,500 kg of seaweed with time of culture for 90 days. The results obtained in treatment A showed that daily growth rate of tiger shrimp: 5.66%; milkfish : 1.84% and seaweed : 2.3%. Production of tiger shrimp 165 k, milk fish : 417 kg, and seaweed 4285.7 kg dry-wet. Daily growth rate in pond B is tiger prawn: 5.21%; seaweed : 2.2%), production of tiger shrimp: 127 kg and seaweed 3,985.7 kg. While the daily growth rate for pond C is milk fish:1.91% and seaweed : 1.08% with a production of 450 kg and 3,085 kg dry-wet. Analysis economic showed that total production and income of pond C has higher revenues followed by B and A. Keywords : Policulture technology, tiger shrimp, milkfish, seaweed, daily growth rate, production.